Efficient CuO/Ag2WO4 photoelectrodes for photoelectrochemical water splitting using solar visible radiation. Issue 17 (11th April 2023) - Mustafa, E.; Dawi, E. A.; Ibupoto, Z. H.; Ibrahim, A. M. M.; Elsukova, A.; Liu, X.; Tahira, A.; Adam, R. E.; Willander, M.; Nur, O.
Abstract : Using the hydrothermal method followed by the SILAR method, synthesis of CuO/Ag2 WO4 -5 photocathode that is effective for PEC water splitting when illuminated by solar light is provided. Abstract : Water splitting energy production relies heavily on the development of high-performance photoelectrochemical cells (PECs). Among the most highly regarded semiconductor materials, cupric oxide (CuO) is an excellent photocathode material. Pristine CuO does not perform well as a photocathode due to its tendency to recombine electrons and holes rapidly. Photocathodes with high efficiency can be produced by developing CuO-based composite systems. The aim of our research is to develop an Ag2 WO4 /CuO composite by incorporating silver tungstate (Ag2 WO4 ) nanoparticles onto hydrothermally grown CuO nanoleaves (NLs) by successive ionic layer adsorption and reaction (SILAR). To prepare CuO/Ag2 WO4 composites, SILAR was used in conjunction with different Ag2 WO4 nanoparticle deposition cycles. Physicochemical characterization reveals well-defined nanoleaves morphologies with tailored surface compositions. Composite CuO/Ag2 WO4 crystal structures are governed by the monoclinic phase of CuO and the hexagonal phase of Ag2 WO4 . It has been demonstrated that the CuO/Ag2 WO4 composite has outstanding performance in the PEC water splitting process when used with five cycles. In the CuO/Ag2 WO4 photocathode, water splitting activity is observed at low overpotential and high photocurrent density, indicating that the reaction takes place at low energy barriers. Several factors contribute to PEC performance in composites. These factors include the high density of surface active sites, the high charge separation rate, the presence of favourable surface defects, and the synergy of CuO and Ag2 WO4 photoreaction. By using SILAR, silver tungstate can be deposited onto semiconducting materials with strong visible absorption, enabling the development of energy-efficient photocathodes.